The Use of Technology in Evaluation Practice - Vanessa Jamieson; Tarek Azzam (Journal of MultiDisciplinary Evaluation)
Background: Evaluation practice is no longer limited to pencil and paper questionnaires, today technological advances allow evaluators to collect data with handheld devices, visualize information in interactive ways, and communicate instantaneously with stakeholders across the globe. These advances have changed how we conduct our practice and they will continue to redefine how we design our evaluations, interact with stakeholders, and communicate our findings. There are few published articles that examine the interface between evaluation and technology and this study represents an initial attempt at examining the technological tools that evaluators use in their practice, the reasons they are adopted, and future technological interest of practicing evaluators.